Abnormal alpha-synuclein reduces nigral voltage-dependent anion channel 1 in sporadic and experimental Parkinson's disease - Chu, Yaping; Goldman, Jennifer G.; Kelly, Leo; He, Yinzhen; Waliczek, Tracy; Kordower, Jeffrey H. (Neurobiology of disease, 2014)
Both the misfolding of α-synuclein and mitochondrial dysfunction are considered two major contributors to Parkinson's disease (PD). However, the relationship between the two in normal and PD states remains unclear. Here, we report that voltage-dependent anion channel 1 (VDAC1), a major component of the outer mitochondrial membrane known to regulate mitochondrial functions, is down-regulated in response to α-synuclein accumulation and aggregation. Stereological analysis revealed that 58.33% of the neurons were VDAC1 immunoreactive in the remaining neuromelanin laden neurons in the PD group while 87.48% of the nigral neurons were VDAC1 immunoreactive in the age-matched control group. The relative levels of VDAC1 were significantly decreased in PD nigral neurons when compared to age-matched controls. In PD, this decrease was significantly greater in nigral neurons with α-synuclein inclusions. VDAC1 was observed in fibers with granular α-synuclein but not in fibers with aggregated α-synuclein. Viral vector-mediated overexpression of mutant human α-synuclein (A30P) in rats resulted in significantly decreased VDAC1 in nigral neurons and striatal fibers. These results indicate that mitochondrial function associated with VDAC1 is decreased in sporadic and experimental PD, and this decrease is associated with α-synuclein accumulation and aggregation. •VDAC1 is decreased in sporadic and experimental Parkinson's disease.•VDAC1 is down-regulated in nigral neurons with α-synuclein inclusions.•VDAC1 was present in fibers with granular but not aggregated α-synuclein.•α-Synuclein overexpression results in reduction of VDAC1.